THE EFFECT OF ASYMMETRICAL INFORMATION AND RISK ATTITUDE ON INCENTIVE SCHEMES: A CONTINGENCY APPROAC - JOGIYANTO HARTONO; BAMBANG RIYANTO LS (Journal of Indonesian Economy and Business (JIEB), 1997)
This paper discusses several incentive models. Some models are only appropriate for risk neutral agents, but not for risk averse agents. For certain circumstances, a quadratic model is needed to replace a linear model The choice of which model is the appropriate one is the question addressed by this paper. Risk attitude and several aspects of asymmetric information will be discussed.